IRRITABLE BOWEL SYNDROME IN CHILDREN AND ADOLESCENTS - P.L. Shcherbakov (Вопросы современной педиатрии)
The article is dedicated to one of the most widespread functional disorders of the gastrointestinal tract — irritable bowel syndrome. Ethiology, pathogenesis, modern classification of the syndrome, principles and methods of treatment of irritablebowel syndrome with diarrhea usually predominating are described.Key words: irritable bowel syndrome, diarrhea, diosmektite, children, adolescents.